Evaluación de la incidencia del manejo ecológico en la productividad del cultivo del maíz, en el barrio las Flores de la parroquia Panguintza del cantón Centinela Del Cóndor. - Alvarez Herrera, Mario Javier (2015)
This present study as an underdegree project work, it was done on Panguintza community, Centinela the Condor Canton, Zamora Chinchipe Province. According to the proposed research theme "Evaluation of the impact of ecological management in the productivity of maize, in Las Flores neighborhood, Panguintza Parish, Centinela the Condor Canton". The objectives set were: to implement a demonstrative plot of organic maize in Las Flores neighborhood, Panguintza Parish, Centinela the Condor Canton, and to assess the level of productivity and profitability of the plot produced with ecological approach and to socialize the results at Community level and institutional. To fullfil the first objective it was implemented a demonstrative plots of 10 x 10 m, applying three treatments: First treatment (cultivation normally produced in the area), second treatment (Compost + organic product (biol + fertígro + potassium + lemon), and the third treatment (Compost + organic product (biol + fertígro + potassium + lemon) + Traps), with the purpose to know which one provides the best productivity and profitability. According to the results obtained were: variable percentage of organic matter appearing at a percentage of 3.08% of MO, in relation to the ground after seeding which has a percentage of 3.43% of MO, on variables infested plants infested pests pests and diseases, statistical significance between treatments is appreciated and also against the witness excelling in both the T3. Productivity variable is synthesized to the yield achieved with Treatment 3 (3,700 kg / ha) is considerably higher, with respect to treatments 2 (3,400 kg / ha) and Treatments 1 (3,000 kg / ha).